Efficacy of high-flow nasal oxygenation compared with laryngeal mask airway in children undergoing ambulatory oral surgery under deep sedation: A randomized controlled non-inferiority trial - Ran, Longkuan; Huang, Guijin; Yao, Ying; Wu, Yujia; Zhang, Chao; Wang, Yan; Yu, Cong (Frontiers in Medicine, 2022)
Background High-flow nasal oxygenation (HFNO) has been suggested as an alternative oxygenation method during procedural sedation. This randomized, non-inferiority trial evaluated the safety and efficacy of HFNO compared with laryngeal mask airway (LMA) in pediatric ambulatory oral surgery under deep sedation. Methods In total, 120 children aged 2–7 years (weight: 10–30 kg) were equally assigned into two groups, namely, HFNO with propofol total intravenous anesthesia infusion (HFNO-IV) or LMA with propofol total intravenous anesthesia infusion (LMA-IV). The primary objective was to monitor carbon dioxide (CO2) accumulation during perioperative surgery. Secondary objectives included monitoring transcutaneous oxygen saturation, grade exposure to the surgical field, perioperative adverse events, or other events. The predefined non-inferiority margin was 7 mmHg. During the COVID-19 pandemic, a novel WeChat applet was implemented to gather follow-up data after discharge. Results Non-inferiority could be declared for HFNO relative to LMA (mean difference in transcutaneous CO2 (TcCO2) = −1.4 mmHg, 95% CI: −2.9, 0.1 mmHg; P > 0.05). The pre-surgical TcCO2 of the HFNO-IV group (45.4 ± 4.5 mmHg) was similar to that of the LMA-IV group (44.0 ± 3.5 mmHg), within the clinically acceptable normal range. All the children maintained SpO2 levels of >97%. The surgical field exposure score of the HFNO group was significantly better than that of the LMA group. There was no significant difference between the two groups regarding risk or adverse events. Conclusion HFNO was not inferior to LMA for maintaining oxygenation and ventilation in patients undergoing pediatric ambulatory oral surgery under deep sedation under strict isolation from the oral cavity to the upper airway.